GOOGLE FORMS AS AN EFL ASSESSMENT TOOL: POSITIVE FEATURES AND LIMITATIONS - Angela Bayu Pertama Sari; Dwi Iswahyuni; Sri Rejeki; Sutanto Sutanto (Premise: Journal of English Education and Applied Linguistics, 2020)
This study presents an assessment tool in which it aims to investigate the positive features and limitations of Google forms as an EFL assessment tool. The research method used in this study is a descriptive qualitative study in which the instruments employed are class activity log and observation checklist. Moreover, the participants are 240 non-English major students. The results of the study showed that there are 5 positive features and 2 limitations of Google Forms as an EFL assessment tools.  It can be concluded that the positive features of Google forms as an EFL assessment tool are in terms of efficiency in time and energy, conformity to the students’ characteristics, less cost, detail result, and helpful features. In other words, the significant implication is that the use of Google Forms as an assessment tool can alleviate the lecturer’s workload. Furthermore, the limitations deal with scoring and tools issues.